THEMATIC LEARNING BASED ON CHARACTER EDUCATION IN SD NEGERI 122358 PEMATANG SIANTAR - Sijabat, Osco Parmonangan (Unversitas Katolik Santo Thomas, 2022)
This study aims to obtain a thematic based character education learning model at the elementary school level. The learning model consists of devices and guides student learning. The acquisition of the model began with a literature study, observations were made during this research, the analysis was then compiled and a model design design was developed and continued with limited testing in first grade elementary schools. The results of the trial show that the prepared model design still needs to be refined, especially in student books. This is because at the time of the trial, the guidelines were still not able to guide students in learning. Sentences in this book are still biased. In the interview, students were disturbed by using the student guide. Apart from the unusual usage as well as the user manual is not very clear. But overall, this model is useful as a guide in determining steps or policies related to improving the quality of learning at the primary school level, specifically for first graders.